Characterisation of Li2SnO3 by solution evaporation method using nitric acid as chelating agent - Majid, Siti Rohana; Arof, Abdul Kariem; Teo, L.P.; Buraidah, M.H.; Alias, N.A.; Kufian, M.Z. (Springer Verlag (Germany), 2011)
Lithium stannate (Li2SnO3) was prepared by solution evaporation method utilising acetates of tin and lithium as starting materials. From thermogravimetric analysis, no weight loss was observed at temperatures above 800 degrees C. The Li2SnO3 precursor was then sintered at 800 degrees C for 5, 6, 7, 8 and 9 h, respectively. X-ray diffraction confirmed the sample to be Li2SnO3 with a monoclinic cell structure. The lattice parameters, volume and density of Li2SnO3 at different sintering hours were calculated. Sintering the precursor at 800 degrees C for 9 h produced Li2SnO3 with lattice parameters a=5.302 angstrom, b=9.167 angstrom and c=10.032 angstrom, volume of 479.922 angstrom(3) and density of 4.999 g cm(-3). The product was used as anode active material in the fabrication of a lithium half cell. The Li2SnO3//1M LiPF6/ethylene carbonate/diethyl carbonate (v/v=1 : 2)//Li cell exhibited an initial discharge capacity of 363.1 mA h g(-1).